Electromagnetic‐circuit co‐simulation of very fast transient overvoltage in gas‐insulated switches. (December 2016) - Liu, Ying; Chao, Hsuehyung; Xie, Yongjun; Wu, Dongwei
Abstract : The very fast transient overvoltage (VFTO) originating from operations of an isolating switch in a gas‐insulated switch (GIS) will cause dangerous interference to the switch and its peripherals. Aiming at the engineering issue, a collaborative simulation method by field‐circuit‐wave of VFTO radiation interference is proposed in this paper. With a combination of project cases, the GIS equivalent circuit is first extracted by means of quasistatic electromagnetic (EM) field analysis. Furthermore, the equivalent time‐varying voltage source of VFTO is obtained by associating the time‐varying resistance model of the switching arc and the broadband circuit method. Finally, using the transient full‐wave technique in the time domain, the spatial EM interference by VFTO is simulated. It turns out that this method has high significance to the high‐voltage switch design. © 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.